EXPLORING THE USE OF INPUT IN SPEAKING LESSONS AT FELTE, ULIS, VNU – A CASE STUDY - Phan, Thị Toán (2021)
This study investigates the mutual support of teacher instruction and input in speaking lessons in two first-year classes at Department I, FELTE, ULIS, VNU. A multiple case study design and the qualitative approach were applied to take an in-depth investigation into the problem. Five observations with recordings and observation schemes were conducted in each class to discover the way the teachers guided the students with the input in terms of eliciting questions and instruction giving. Moreover, the teachers’ perceptions of the effectiveness of input using were measured by their responses in the interviews after each observation. The students’ perceptions were explored through the reflection sheets delivered at the end of the observation process and the retrospect interviews. The data collected were coded and then decoded and analyzed under each research question. The study found that elaborated input was used with teachers’ guidance in almost all the activities. Although the students are very satisfied with the input using in class, it is recommended that teacher instruction and input selection should be improved. More kinds of input such as pre-modified and enhance input or meaningful output should be used to catch the students’ attention and motivate them to think. The input should be more challenging with useful target language items. The teachers need to refer more to the principles of effective eliciting and instructing to make sure the students understand and benefit from the input